A unique permeate gap membrane distillation system for combined fresh water and power production. (February 2019) - Mahmoudi, Farzaneh; Pishbin, Mohammad E.; Date, Abhijit; Akbarzadeh, Aliakbar
Abstract: The low-energy consumption process appears as one of the most dominant priority for sustainable fresh water production in recent years. Membrane distillation ( MD ) can be adapted effectively for water desalination due to lower operating temperature and ability to integrate to low grade waste heat. In this work, the feasibility of combined water and power production ( CWP ) is investigated by a unique permeate gap ( PGMD ) module. The permeate gap hydraulic pressure is controlled by connecting the permeate outlet to a sealed pressurized tank. Furthermore, the effect of permeate hydraulic pressure on the permeate flux and power density are explored experimentally. The maximum hydraulic pressure within this setup by polyvinylidene difluoride ( PVDF ) membrane was around 2 bar. It is demonstrated that under 80 °C and 15 °C of the fluid bulk temperatures in the inlet of hot and cold sides, respectively an optimum permeates hydraulic pressure of 1.1 bar, 12.5 kg/m 2 h of permeate flux, 0.4 W/m 2 of power density and 0.03 kWh/m 3 of specific energy production ( SEP ) are achievable. This capacity of power generation has been accompanied by around 50% permeate flux reduction. The achieved results propose the system potential to produce higher SEP rate, via implementation of the advanced hydrophobic membranes with the higher-pressure resistance feature.